The due process of law - Denning, Alfred Thompson Denning (London ; Woburn, Mass. : Butterworths, 1980)
The measures authorised by the law so as to keep the streams of justice pure, to see that trials and enquiries are fairly conducted, that arrests and searches are properly made, that lawful remedies are available.
Includes bibliographical references and index.
ocf 29/08/2018
Loans
Keywords: Due process of law; Great Britain